Meadow management hay yields and nutritive value in the Mediterranean mountain regions of the Northeast of Portugal - Pires, Jaime (2011)
To evaluate the possibility of improving hay nutritive value, six hay meadows were studied in the Northeast of Portugal from 1998 to 2000. The treatments were fertilization rates of O, 75 and 150 kg N/ha/y in combination with two cutting/grazing regimes: the usual for the area (NG) and a larger spring grazing period with meadows closed off for hay three weeks later (LG). Their effects on crude protein content, in vitro organic matter digestibility, and dry-matter, crude protein and metabolizable energy yields were evaluated. The treatments studied significantly influenced the parameters evaluated. Late spring grazing induced the greatest changes in the highest yielding meadows (M3 and M5) increasing nutritive values but decreasing the DM yield (-2t DM/ha, + 1 % CP and +3% IVOMD). However, the positive influences on CP content and IVOMD are not high enough to overcome the low values (Iess than 10% CP and 50% IVOMD) observed in meadows with hay growth periods longer than 60-70 days